India-China border issue : compilation of facts and views - Basu, B. K.; Bosu, Jyotirmoy (Desh-o-Dunia Publishers : Distributors, National Book Agency, 1981)
Comprises articles, newspaper clippings, and extracts from Indian parliamentary debates.